2020
DOI: 10.1080/17461391.2020.1753816
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of linear, hyperbolic and double‐hyperbolic models to assess the force–velocity relationship in multi‐joint exercises

Abstract: This study assessed the validity of linear, hyperbolic and double-hyperbolic models to fit measured force-velocity (F-V) data in multi-joint exercises and the influence of muscle excitation on the F-V relationship. The force-joint angle and F-V relationships were assessed in 10 cross-training athletes and 14 recreationally resistance-trained subjects in the unilateral leg press (LP) and bilateral bench press (BP) exercises, respectively. A force plate and a linear encoder were installed to register external fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…Cuk et al 2014;Jaric 2015), which validates the physiological relevance of Pmax-L. In the present study, curvilinear models showed lower value of Pmax than linear model (Table 3) in contrast to similar or higher values of Pmax previously reported (18,20). The higher Pmax values obtained from curvilinear models were certainly due to a lack of experimental force and velocity collected below 50 %F0 when fitting the linear model, which have led a lower v0-L and, in turn, a lower Pmax-L (20).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Cuk et al 2014;Jaric 2015), which validates the physiological relevance of Pmax-L. In the present study, curvilinear models showed lower value of Pmax than linear model (Table 3) in contrast to similar or higher values of Pmax previously reported (18,20). The higher Pmax values obtained from curvilinear models were certainly due to a lack of experimental force and velocity collected below 50 %F0 when fitting the linear model, which have led a lower v0-L and, in turn, a lower Pmax-L (20).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, curvilinear models showed lower value of Pmax than linear model (Table 3) in contrast to similar or higher values of Pmax previously reported (18,20). The higher Pmax values obtained from curvilinear models were certainly due to a lack of experimental force and velocity collected below 50 %F0 when fitting the linear model, which have led a lower v0-L and, in turn, a lower Pmax-L (20). Aside from this methodology, the similar values of Pmax were obtained between linear and curvilinear models due to the high number of resistive/loading conditions around the optimal velocity condition (18).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations